PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR WILAYAH DIREKTORAT JENDERAL PERBENDAHARAAN DI KOTA KUPANG - Yunita Anggraini Madi; Darti Djuharni (Politeknik Negeri Malang, 2017)
This study aims to find out how big the influence of Leadership Style on Employee Performance; and How big influence of Work Motivation to Employee Work Achievement; The population in this study is all employees of Regional Office of Directorate General of Treasury in Kupang city. The sample in this research is 52 employees. Data collection techniques used in this study are questionnaires, observations and documentation. The results of the study showed that: 1) There is a positive and significant influence of Leadership Style on Employee Performance, and There is a positive and significant influence Motivation Work on Job Performance Employees. In addition There are positive and significant influence of Leadership Style and Work Motivation collectively towards Employee Work Achievement.